2020
DOI: 10.3389/fpsyt.2020.00212
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural and Contextual Adaptation Process of an Intervention to Reduce Psychological Distress in Young Adolescents Living in Lebanon

Abstract: Armed conflict leads to increased risk of emotional distress among children and adolescents, and increased exposure to significant daily stressors such as poverty and community and family violence. Unfortunately, these increased risks usually occur in the context of largely unavailable mental health services. There is growing empirical support that evidence-based treatment techniques can be adapted and delivered by nonspecialists with high fidelity and effectiveness. However, in order to improve feasibility, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…To further prevent this in the future, and if time and resources allow, cultural adaptations can also make use of other methods for adapting case studies. Some examples of these methods include: (1) cognitive interviewing for adapting case studies as described in the DIME methodology and as explained by Brown, et al [62]; (2) presenting a focus group discussion with a blank template of how a case example should be structured so they can collaboratively develop an example based on experience; (3) developing case examples through the use of Forum Theatre or Theatre of The Oppressed [19,63] or (4) employing elicitation techniques for cultural domain analysis [64]. A limitation of the fourth step of this process adaptation was the absence of a baseline measure of the Cultural Relevance Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…To further prevent this in the future, and if time and resources allow, cultural adaptations can also make use of other methods for adapting case studies. Some examples of these methods include: (1) cognitive interviewing for adapting case studies as described in the DIME methodology and as explained by Brown, et al [62]; (2) presenting a focus group discussion with a blank template of how a case example should be structured so they can collaboratively develop an example based on experience; (3) developing case examples through the use of Forum Theatre or Theatre of The Oppressed [19,63] or (4) employing elicitation techniques for cultural domain analysis [64]. A limitation of the fourth step of this process adaptation was the absence of a baseline measure of the Cultural Relevance Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The screening interview with adolescents will consist of the PSC-17 (adolescent report), a brief version of the 35-item PSC measuring symptoms of internalising and externalising difficulties in children and adolescents [ 12 ]. The tool has been validated with young adolescents in Lebanon, using semi-structured interviews with psychiatrists as the gold standard [ 13 ], and a cut-off of 12 or more is indicative of a need for psychosocial treatment. The family will be eligible to take part if at least one adolescent screens positive on the PSC-17.…”
Section: Methodsmentioning
confidence: 99%
“…The total PSC-35 score is obtained by summing scores of individual items and ranges from 0 to 70. In a validation study in Lebanon, the measure showed high internal consistency ( σ = .80), convergent validity, test-retest reliability, and concurrent validity with psychiatrist clinical assessments [ 13 ]. The 17 items of the PSC-17 are identical to those in the PSC-35, and therefore at baseline, screening scores for adolescents on these items will be used, and only the remaining 18 items assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts were not duplicated following coordination by local community leaders ( Nuwayhid et al., 2011 ). Others also highlight the importance of cultural and contextual adaptations to interventions in various countries including Lebanon ( Brown et al., 2020 ).…”
Section: Lessons From Responses To Previous Adverse Experiences In Lebanonmentioning
confidence: 99%